A SCOPING REVIEW OF TRAUMA-INFORMED EARLY LEARNING AND CHILD CARE IN CANADA: A CRITICAL ANALYSIS - Slemon, Allie; Gerlach, Alison J.; Moosa-Mitha, Mehmoona; Macasaquit, Mariel (International Journal of Child, Youth and Family Studies, 2025)
Among child care policymakers, government officials, and providers alike, there is growing interest in mitigating the impacts of adversity and trauma in children’s early years. While emerging literature examines the prevalence and impacts of traumatic events on the lives of children and families, a focus on trauma-informed approaches within the early learning and child care sector remains nascent. This scoping review examines the current state of knowledge in peer-reviewed and grey literature on trauma-informed approaches in the early learning and child care sector in Canada. Critical analysis of the findings highlights a concerning gap in the empirical evidence on trauma-informed approaches, obscure and individualistic understandings of trauma, and considerable variance in how trauma-informed approaches are implemented. We call for explicit shifts toward understanding trauma as inclusive of interpersonal and structural forms of trauma and violence and a broader scope of “trauma- and violence-informed child care” (TVICC).